Rydberg electron focused by Coulomb potential to enhance high-order harmonic generation via the chirped laser. (8th January 2019) - Lu, Jinjun; Li, Qianguang; He, Lixin; Qiao, Haoxue
Abstract: We theoretically study the high-order harmonic generation (HHG) from Rydberg hydrogen atom driven by a mid-infrared linearly polarized chirped laser pulse. It is shown that the high-order harmonic spectrum demonstrates an excessive high-yield broad-band supercontinuum. Based on the analyses of quantum-mechanical and classical models, it is found that the enhancement is caused by the motion of the Rydberg electron perpendicular to the polarization direction of the chirped laser pulse, which is induced by the attraction of the nucleus and initial orbital velocity of the Rydberg electron. This mechanism is different from the previous study (Chen et al 2015 Phys. Rev. A 91 043403), in which the motion of the Rydberg electron perpendicular to the polarization direction has little contribution to HHG.